Early modern knowledge societies as affective economies
1 online resource (xv, 335 pages)
Keywords: "Early Modern Knowledge Societies as Affective Economies researches the development of knowledge economies in Early Modern Europe. Starting with the Southern and Northern Netherlands as important early hubs for marketing knowledge, it analyzes knowledge economies in the dynamics of a globalizing world. Introducing the reader to different perspectives on how knowledge markets operated from both an economic and cultural perspective, this book will be of great use to students, graduates and scholars of early modern history, economic history, the history of emotions, and the history of the Low Countries"--